Performance of multiple-feed metasurface antennas with different numbers of patch cells and different substrate thicknesses - Hussain, Niamat; Park, Ikmo (Applied Computational Electromagnetics Society Journal, 2018)
The design and performance of low-profile, multiple-feed metasurface antennas with different numbers of patch cells and different substrate thicknesses at a terahertz frequency are presented in this paper. The utilized antenna designs consist of a periodic array (N × M) metallic square-patch metasurface and a planar feeding structure, which are both patterned on an electrically thin, high-permittivity GaAs substrate. The antenna gain increased in a linear fashion with an increasing number of patch cells, which were directly fed by the slit feedline. A 3-dB gain increment was observed irrespective of the substrate thickness when the number of patch cells was doubled. However, the 3-dB gain bandwidth as well as the radiation efficiency changed significantly with varying substrate thicknesses. The described antenna structure offers useful characteristics by means of a combination of different substrate thicknesses and patch numbers. In addition, the proposed antenna design features a number of benefits, including a low profile, mechanical robustness, easy integration into circuit boards, and excellent suitability for low-cost mass production.
Keywords: Different substrates; Gain bandwidth; Mechanical robustness; Metasurface; Radiation efficiency; Substrate thickness; Terahertz antennas; Terahertz frequencies; Antenna array; Metamaterials; Metasurface; Terahertz antennas; Wide gain bandwidth